PEMBUATAN PATI DARI RIMPANG LENGKUAS, TEMULAWAK, TEMUKUNCI SERTA KARAKTERISASINYA - Nasution, Pandapotan; Suharyanisa, Suharyanisa; Situmorang, Manahan; Manihuruk, Nurpita Putri (Jurnal Farmanesia, 2021)
The rhizome is part of the plant for food reserves, including storing carbohydrates (starch), therefore rhizomes of Galangal, Curcuma, Fingerroot rhizome can be used as a source of starch. This study used an exploratory method which included isolation of starch from Galangal, Curcuma, Fingerroot Rhizome, macroscopic examination, microscopic examination, sample collection, sample processing, and examination of the characterization of starch. The results of starch characterization obtained yields for Galangal starch 2.6%, Curcuma starch 5.4%, Fingerroot rhizome starch 4.1%; determination of total ash content for Galangal starch 1.4%; Curcuma starch 2.0%, Fingerroot rhizome starch 1.0%; determination of drying shrinkage for 1.8% Galangal starch, 2.4% Curcuma starch, 3.2% Fingerroot rhizome starch; determination of acid-insoluble ash content for 0.6% Galangal starch, 0.7% Curcuma starch, 0.7%Fingerroot rhizome starch.